Unreal Engine 5 : the complete beginner's course. - Nixon, David (Packt Publishing, 2023)
Want to learn how to make video games? Then why not make games with the exact same software used to develop hit titles such as Fortnite, Batman: Arkham Asylum, Gears of War, and Mass Effect--the state-of-the-art Unreal Engine. By beginning your game development journey with Unreal Engine 5, you will be learning the same engine that the pros use. In this introductory course, you will begin by getting Unreal Engine 5 up and running and then learning the fundamentals of game development. After you master the basics, you will learn the skills needed to craft beautiful environments to stage your games in. You will learn how to script logic for your games, which will help you define game rules; keep track of data such as health and inventory; and create playable characters. This course will teach you how physics works in Unreal Engine 5 and how to handle collisions. You will learn how to create user interfaces, so you can add menus, load screens, and HUDs to your game. You will learn how audio works within the Engine so that you can add music, dialogue, and sound effects. And finally, you will learn how to package your game so that it can be played on other computers and game consoles. By the end of this course, you will gain all the skills necessary to bring your ideas to life and create your own video games using the cutting-edge Unreal Engine 5. What You Will Learn Learn game development using Unreal Engine 5 Learn the fundamentals of game design Understand how to use Unreal Engine 5 Build realistic-looking environments for games to take place in Define custom inputs and movements to control characters Script logic to define gameplay without needing to know how to code Audience This video game development course is for absolute beginners who are interested in making games and learning how to design a game from scratch using UE5. This course is designed for those who want to become professionals using Unreal Engine 5. No programming experience is required. About The Author David Nixon: David Nixon is a professional software developer with a degree in computer science from Florida Atlantic University. He is a lifelong video game aficionado who started with the Atari 2600 and never looked back. He enjoys music, reading, and sports in his spare time.